Metabolism Of Iron In Breast Milk Of Women During Different Stage Of Lactation - Yunus Ruziev, Zuxro Ubaydullaeva, Asatullo Rajabov (International Journal of Advanced Science and Technology, 2020)
Breast milk is the only source of nutrients that contains all the components of normal growth and development of children. That is why breastfeeding is so important for a healthy baby. In the dynamics of lactation, the analysis of iron, binding of iron, breastfeeding properties and quantitative indicators of lactoferrin have great scientific and practical importance.